Critical couplings in topological-insulator waveguide-resonator systems observed in elastic waves. Issue 2 (23rd October 2020) - Yu, Si-Yuan; He, Cheng; Sun, Xiao-Chen; Wang, Hong-Fei; Wang, Ji-Qian; Zhang, Zi-Dong; Xie, Bi-Ye; Tian, Yuan; Lu, Ming-Hui; Chen, Yan-Feng
Abstract: Waveguides and resonators are core components in the large-scale integration of electronics, photonics and phononics, both in existing and future scenarios. In certain situations, there is critical coupling of the two components; i.e. no energy passes through the waveguide after the incoming wave couples into the resonator. The transmission spectral characteristics resulting from this phenomenon are highly advantageous for signal filtering, switching, multiplexing and sensing. In the present study, adopting an elastic-wave platform, we introduce topological insulator (TI), a remarkable achievement in condensed matter physics over the past decade, into a classical waveguide-ring-resonator configuration. Along with basic similarities with classical systems, a TI system has important differences and advantages, mostly owing to the spin-momentum locked transmission states at the TI boundaries. As an example, a two-port TI waveguide resonator can fundamentally eliminate upstream reflections while completely retaining useful transmission spectral characteristics, and maximize the energy in the resonator, with possible applications being novel signal processing, gyro/sensing, lasering, energy harvesting and intense wave–matter interactions, using phonons, photons or even electrons. The present work further enhances confidence in using topological protection for practical device performance and functionalities, especially considering the crucial advantage of introducing (pseudo)spins to existing conventional configurations. More in-depth research on advancing phononics/photonics, especially on-chip, is foreseen. Abstract : A new, topologically empowered, planar waveguide-resonator system was demonstrated, exhibiting unique advantages over traditional designs.